Implementing Web Content Accessibility Guidelines for Disability-Friendly Scholarship Websites in Indonesia - Poedjadi, Maudy Rizkiana; Lestari, Gita Cahyani; Lisnarini, Naurah; Umar, Muhammad Novsyaroni (PRofesi Humas, 2026)
Background: The low level of disability education is currently a public concern. One way to improve it is to provide financial assistance in education. Seeing this phenomenon, the ministries established two special scholarships for people with disabilities: the ADik scholarship, administered by the Ministry of Higher Education, Science, and Technology (Kemdiktisaintek), and the LPDP Affirmation Scholarship, administered by the Ministry of Finance (Kemenkeu). These scholarships can be accessed through the websites of both ministries. However, to target these scholarships effectively, the government’s public relations (PR) must ensure the website meets the technological and information needs of people with disabilities. Accommodating this information and technology is a form of good e-government. Purpose: This study aims to evaluate the accessibility of scholarship websites for people with disabilities by analyzing accessibility components using four assessment tools: SiteAnalyzer, AEL Data, Accessibility Cloud, and Silktide Accessibility Checker. It explains how well these government websites comply with Web Content Accessibility Guidelines (WCAG) and whether they adequately support users with disabilities in accessing scholarship information. Result: Based on the analysis of the four tools, neither scholarship website is fully accessible, showing significant WCAG violations. The SiteAnalyzer classified both as “unsafe,” while Silktide found 394 violations on LPDP and 152 on ADik across WCAG Levels A, AA, and AAA. These extensive failures to meet accessibility criteria indicate a deficit in the Digital Public Relations function, specifically in upholding the principles of communication accountability and transparency toward the disability public. Implication: Technology and information that are not properly accommodated compromise the scholarship’s objective and hinder the right to equal access for persons with disabilities. This highlights the urgent necessity for PR professionals to take a strategic role in advocating for and prioritizing comprehensive WCAG implementation to mitigate institutional risk, build trust, and ensure inclusive public service delivery.